2022
DOI: 10.1007/s44189-022-00008-2
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical evaluation of stack-based thermoacoustic refrigerators

Abstract: Standing wave thermoacoustic refrigerator uses stack, is the heart of the thermoacoustic cooling system. The porous stack in the resonator tube develops temperature difference across the stack for heat pumping upon loudspeaker sound interaction of oscillating gas. In this paper, the optimization of stack-heat exchangers system and resonator is discussed using linear thermoacoustic theory for better COP and cooling power of refrigerator. The loudspeaker is assumed to provide the required acoustic power with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In addition, it is found that the temperature gradient is sensitive to the thermophysical proprieties of working gas; this temperature was the lower for nitrogen followed by helium and argon. other more recent studies have been developed to study the efficiency of the stack either by optimizing its geometry or by using a different working fluid [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is found that the temperature gradient is sensitive to the thermophysical proprieties of working gas; this temperature was the lower for nitrogen followed by helium and argon. other more recent studies have been developed to study the efficiency of the stack either by optimizing its geometry or by using a different working fluid [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%